Sunday

April 20, 2014

April 20, 2014

Posted by **centya** on Friday, December 14, 2012 at 7:47am.

- maths -
**Steve**, Friday, December 14, 2012 at 1:00pmor, as we say in English, "solve for d"

e = √d/ab

eab = √d

(eab)^2 = d

if you were careless with parentheses, and meant

e = √(d/ab)

e^2 = d/ab

abe^2 = d

**Related Questions**

maths - How do i rearrange the equation to make d the subject. e = d/ab (d/ab ...

Year 11 maths - My teacher said If x-2(square root xy)=9-4(square root 2) so ...

math - determine the area of triangle abc when side ab= square root of x, side ...

Algebra - Rationalize each expression by building perfect nth root factors for ...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

Math simplifying mixed radicals - Please help me simplify these following mixed...

Math - Just need some help... Directions: Multiply or raise to the power as ...

Math - What is the square root of 12? 3.464 Well, that's true, but you could ...

Math - If im changing the subject of an equation to make x the subject with x^2=...

Math - Using the distance formula I have to prove that ABC are colinear. A(-1, -...